Antibody specificity and promiscuity. Issue 3 (5th February 2019) - Jain, Deepti; Salunke, Dinakar M.
Abstract : The immune system is capable of making antibodies against anything that is foreign, yet it does not react against components of self. In that sense, a fundamental requirement of the body's immune defense is specificity. Remarkably, this ability to specifically attack foreign antigens is directed even against antigens that have not been encountered a priori by the immune system. The specificity of an antibody for the foreign antigen evolves through an iterative process of somatic mutations followed by selection. There is, however, accumulating evidence that the antibodies are often functionally promiscuous or multi-specific which can lead to their binding to more than one antigen. An important cause of antibody cross-reactivity is molecular mimicry. Molecular mimicry has been implicated in the generation of autoimmune response. When foreign antigen shares similarity with the component of self, the antibodies generated could result in an autoimmune response. The focus of this review is to capture the contrast between specificity and promiscuity and the structural mechanisms employed by the antibodies to accomplish promiscuity, at the molecular level. The conundrum between the specificity of the immune system for foreign antigens on the one hand and the multi-reactivity of the antibody on the other has been addressed. Antibody specificity in the context of the rapid evolution of the antigenic determinants and molecular mimicry displayed by antigens are also discussed.